2014
DOI: 10.18404/ijemst.43595
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Taken-As-Shared Understanding for Scientific Explanation: Classroom Norm Perspective

Abstract: The study aimed to investigate whether classroom norm perspective influence the students' capability of elucidating a natural phenomena and beliefs about scientific explanation. In particular, our objective was to explore the process by which the norm for scientific explanation was established and discover how the students' explanation and their beliefs about scientific explanation altered in this process. A case study approach was adopted and a total of 51 students participated in the study. The data has incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The instructor is a high-status actor and has outsize influence over the development of social norms, but they cannot "set" these norms -they must be negotiated through repeated interaction. The dynamic coevolution of beliefs and norms was originally developed in elementary school mathematics courses, and has been seen in undergraduate mathematics and science classes (Dixon et al, 2009;Johnson, 2000;Saglam et al, 2014;Yackel & Rasmussen, 2003;Yackel et al, 2000). In this manuscript, we focus on the PSTs' espoused beliefs about the students' roles, the instructor's role, and the nature of mathematical learning as they reflect on their experiences in this course and imagine their future teaching.…”
Section: Theoretical Framingmentioning
confidence: 99%
“…The instructor is a high-status actor and has outsize influence over the development of social norms, but they cannot "set" these norms -they must be negotiated through repeated interaction. The dynamic coevolution of beliefs and norms was originally developed in elementary school mathematics courses, and has been seen in undergraduate mathematics and science classes (Dixon et al, 2009;Johnson, 2000;Saglam et al, 2014;Yackel & Rasmussen, 2003;Yackel et al, 2000). In this manuscript, we focus on the PSTs' espoused beliefs about the students' roles, the instructor's role, and the nature of mathematical learning as they reflect on their experiences in this course and imagine their future teaching.…”
Section: Theoretical Framingmentioning
confidence: 99%
“…Therefore, it is considered that the explanations of teachers are important in order that the subjects of science lessons are comprehensible and permanent. Hence, especially in science lessons, teachers must explain the subjects related to daily life with causal reasons (Saglam, Karaaslan & Ayas, 2014), and students must be allowed to make explanations. In order to ensure this, it can be stated that teachers first must know what a scientific explanation is and how to make a good scientific explanation.…”
Section: Introductionmentioning
confidence: 99%
“…No study was found in the literature that determines the teachers' beliefs about scientific explanations. In a study by Saglam, Karaaslan & Ayas (2014), primary school teacher candidates' beliefs about scientific explanations were determined. Thus, it is possible to say that the study is unique as it has determined high school teachers' beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations